Frontera, historia y literatura - Jiménez de Báez, Yvette (El Colegio de México, 2012)
First, I attempt define the concept of frontier. On the outside, the externalfrontiers (space changes, social interchange, ethnic and cultural hybridism)impact on individuals and have an influence on their internal frontiers,which are sensitive to the assimilation of different attitudes, feelings, ideas,world views, and diverse cognitive parameters. I then analyze Luis HumbertoCrosthwaite’s narrative, Estrella de la Calle Sexta, which seems to foregroundthe concept of being on the frontier, in both senses, in the NorthernFrontier of Mexico. In doing so, I also reveal the relations between this textand others, and relate them to the social and cultural context of Crosthwaite’sgeneration.